ANALYSIS OF THE DIMENSIONS OF PHYSICAL SELF-CONCEPT BY SEX IN ADOLESCENTES FROM A TYPICAL SPANISH MEDITERRANEAN COMMUNITY - Palomares Cuadros, Juan (2016)
This study examined globally adolescents’ physical self-concept as a function of its components: physical appearance, physical ability, strength, balance, flexibility, and endurance, and as a function of their sex, in a population aged 12-15 from Jaén, Spain. The sample consisted of 296 participants with an average age of 13.03 years. As a measuring tool, an adaptation of the Marsh and Sutherland Physical Self-concept Scale was used. The results revealed that boys rated above girls in most of the items that showed positive self-concept aspects. Conversely, girls scored higher than boys in the majority of negative self-concept items. Our evidence showed significant gender differences related to teenagers’ physical self-concepts; where girls obtained more negative assessments regarding physical self-concepts than boys did, and the latter group was more interested in engaging in physical exercise than the former group.English translation by Jeannette Soto Segura